PENGARUH IKLAN TELEVISI, KUALITAS PELAYANAN, DAN ULASAN PENGGUNA TERHADAP MINAT BELI REMAJA DI DESA PLEMAHAN - Trisna, Putri Trisna Wati; Tjetjep Yusuf Afandi; Efa Wahyu Prastyaningtyas (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This research was motivated by television advertisements, which were considered the main factor influencing the awareness and buying interest of teenagers in Plemahan Village regarding advertised products. Apart from that, the services provided by Shopee through its various features can attract consumers' buying interest. Then, the user review feature is considered when determining purchases, both from positive and negative reviews. This research aims to 1) determine the effect of television advertising on online buying interest on e-commerce sites for teenagers in Plemahan Village, 2) find out the quality of service on online buying interest on e-commerce sites for teenagers in Plemahan Village, 3) determine the influence of user reviews on online buying interest on e-commerce sites for teenagers in Plemahan Village, 4) To find out the influence of television advertising, service quality, and user reviews on online buying interest on e-commerce sites for teenagers in Plemahan Village. This research was conducted using a survey method with a questionnaire as a data collection instrument. The research sample consisted of teenagers in Plemahan Village who actively used the Shopee platform to shop online, totaling 108 respondents using the simple random sampling method. Data analysis used multiple linear regression techniques to evaluate the relationship between the studied variables. The research results show that 1) television advertising partially influences purchase interest with a sig value of 0.000 < 0.05. 2) service quality partially influences purchase interest with a sig value of 0.000 < 0.05. 3) user reviews partially influence purchasing interest with a sig value of 0.006 < 0.05. 4) television advertising, service quality, and user reviews simultaneously influence purchase interest with Fcount = 53.084 and sig value 0.000.